A multispecies competitive nanobody-based ELISA for the detection of antibodies against hepatitis E virus - Arce, Lorena Paola (2023)
The hepatitis E virus (HEV) is an emergent zoonotic virus causing viral hepatitis worldwide. Clinically,hepatitis E is not easily distinguished from other types of acute viral hepatitis. There is a need for HEVdiagnostic assays to detect and prevent interspecies transmission among susceptible populations.Nanobodies (Nbs) are expressed recombinantly in diferent systems, produced with high yields,and have superior physicochemical properties compared with conventional antibodies (Ab). SeveralNbs against ORF2, the capsid protein and main antigen, were selected and produced in E. coli. Nb39and Nb74 specifcally recognized HEV ORF2 (genotypes 3 and 4). A competitive ELISA (cELISA) wasdeveloped and validated using a reference panel of human (n= 86) and swine sera (n= 116) tested incomparison with a commercial kit. The optimal cutof values determined by ROC analysis were 69.16%(human) and 58.76% (swine); the sensitivity and specifcity were high: 97.4% (95% CI 86.5–99.5%) and95.8% (95% CI 86.0–98.8%) for human vs. 100% (95% CI 93.5–100%) and 98.3% (95% CI 91.0–99.7%)for swine. Further, the cELISA detected total anti-HEV antibodies in wild boar, deer, and mice. To ourknowledge, this is the frst report of production of Nbs against HEV-3 ORF2 for diagnostic purposes.